“We Wait”—The Impact of Character Responsiveness and Self Embodiment on Presence and Interest in an Immersive News Experience - Steed, Anthony; Pan, Ye; Watson, Zillah; Slater, Mel (Frontiers in Robotics and AI, 2018)
A virtual reality scenario called 'We Wait' gives people an immersive experience of the plight of refugees waiting to be picked up by a boat on a shore in Turkey to be illegally taken to Europe, crossing a dangerous stretch of sea. This was based on BBC news reporting of the refugee situation, but deliberately depicted as an animation with cartoon-like characters representing the refugees. Of interest was the level of presence that might be experienced by participants and the extent to which the scenario might prompt participants to follow up further information about the refugee crisis. By presence we refer to both Place Illusion, the illusion of being in the rendered space, and Plausibility, the illusion that the unfolding events were really happening. The follow-up was assessed by whether and when participants accessed a web page that contained further information about the refugee crisis after the experiment. Two factors were considered in a balanced between-groups design with 32 participants. The Responsiveness factor was either 'None' or 'Look at'. In the first the virtual characters in the scenario never responded to actions of the participant, and in the second they would occasionally look at the participant after the participant looked at them. The second factor was Embodiment, which was either 'No Body' or 'Body'. In the No Body condition participants had no virtual body, and in the Body condition they would see a virtual body spatially congruent with their own if they looked down towards themselves. The virtual body was animated by the head tracking move the upper body. The results showed that the major factor positively contributing to presence was Responsiveness ('Look at'), and that Embodiment ('Body') may have contributed but to a lesser extent. There were important differences between men and woman in the degree of follow-up, with men more likely to do so than women. The experiment shows that adding in some simple responses in an immersive journalism scenario, where the characters acknowledge the presence of the participant through gaze, can enhance the degree of presence felt by the participants.